Penerapan MFCA Dengan Lean Tools - Erlinda Sholihah; Jaelani Jaelani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the application of Material Flow Cost Accounting (MFCA) as a diagnostic tool and develop methodologies with lean tools that can be validated through their application to case studies in industrial companies. In an effort to become more competitive, the component manufacturing industry needs to find simple and effective solutions that increase productivity while reducing costs. Faced with this reality, companies need to find the right solutions to reduce environmental impact and remain focused on cost control. This study contributes a methodology for integrating MFCA with lean tools in the field of environmental management accounting. This integration enables a comprehensive analysis of the environmental and economic impacts of production, helps companies identify improvement opportunities, and encourages managers to systems of continuous improvement. The study used a review of complementary literature, the development of methods of integrating MFCA and Lean tools. Furthermore, validation is carried out through the application of case studies in industrial companies, which allows the collection of data needed to perform MFCA analysis and calculation models. The integration of MFCA with lean tools provides a comprehensive analysis of the environmental and economic impact of production. The methodology is validated through industry case studies, demonstrating practical applicability and potential benefits. The study also revealed that MFCA analysis has limitations, but when combined with detailed process observations, it can identify inefficiencies that were not detected before. Overall, this methodology enables a shift towards environmentally friendly and low-waste production, and acts as a cycle of continuous improvement to bring production processes closer to ideal optimal levels. The findings suggest that MFCA with lean tools can provide a more comprehensive analysis of the environmental and economic impact of production processes, enabling a shift in production systems towards environmental friendliness and making component waste low. The study provides valuable insights and guidance for companies looking to improve their environmental and economic performance through the integration of MFCA and Lean tools.